Farsighted Rationality in Hedonic Games - G.-Herman Demeze-Jouatsa; Dominik Karos (Dynamic Games and Applications, 2022)
We consider a hedonic coalition formation game in which a coalition chooses for each partition of the player set the probability with which it forms and thereby destroys the current partition. These probabilities are commonly known so that farsighted players know at every partition what future partitions, and hence payoffs, will be reached with what probability. Thus, players can make rational decisions about the moves they support. We show that if coalitions make mistakes with small but positive probability, then there is a behavior profile in which no coalition has a profitable one-shot deviation.
Keywords: C71; C72; 330; Abstract games; Hedonic games; Farsighted stability; Coalition stable equilibrium